Influence of topology of LCST-based graft copolymers on responsive assembling in aqueous media. (9th March 2015) - Guo, Hui; Brûlet, Annie; Rajamohanan, Pattuparambil R.; Marcellan, Alba; Sanson, Nicolas; Hourdet, Dominique
Abstract: This work, based on structure/properties relationships of associating polymers, aims to investigate the role of topology in the self-assembling behavior of responsive graft copolymers. For that purpose, two graft copolymers with inverse topologies were prepared with similar amounts of water-soluble chains (poly( N, N -dimethylacrylamide) = PDMA) and LCST polymer chains (poly( N -isopropylacrylamide) = PNIPA). In pure water, and above 3 wt%, PNIPA- g -PDMA and PDMA- g -PNIPA exhibit very similar macroscopic properties with a sol/gel transition above 35 °C related to the microphase separation of PNIPA sequences. From complementary experiments, performed by DSC, 1 H NMR and small angle neutron scattering, we show that the phase transition of PNIPA is more abrupt when NIPA units are located within the backbone, compared to side-chains. Nevertheless, well above their transition temperature, the two copolymers display very similar bicontinuous structures where PNIPA sequences self aggregate into concentrated percolating domains (about 70 wt% at 60 °C) characterized by a frozen dynamics. On the other hand, when salt or surfactant molecules are added into unentangled semi-dilute aqueous solution, the PNIPA- g -PDMA sample does not percolate anymore above the transition temperature while PDMA- g -PNIPA still demonstrate thermothickening properties that are correlated to the ability of water-soluble PDMA chains to bridge PNIPA aggregates. Graphical abstract: Highlights: Two LCST-based graft copolymers with inverse topologies were prepared from PNIPA and PDMA. Aqueous solution properties were studied by DSC, NMR, neutron scattering and rheology. The two copolymers undergo similar sol/gel transition upon heating in the entangled regime. Transition is more abrupt when PNIPA is used as backbone (PN-D) instead of grafts (PD-N). When unentangled, PN-D chains do not percolate in the presence of salt or surfactant.